1996
DOI: 10.1159/000227578
|View full text |Cite
|
Sign up to set email alerts
|

p53 and MDM2 Expression in Oral Squamous Cell Carcinoma

Abstract: The p53 tumor suppressor gene is the most commonly mutated gene in human cancer and is a frequent abnormality in oral squamous cell carcinoma and its precancerous lesions. MDM2 (murine double minute-2), a new proto-oncogene, may be associated with p53 gene products and may negatively affect the transcriptional activating function of p53. The purpose of this study was to investigate the incidence of MDM2 and its relationship to the expression of p53 in oral squamous cell carcinoma and precancerous lesions. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 18 publications
3
35
0
5
Order By: Relevance
“…MDM2 is another p53 inhibitor present in high levels in HNSC [15][16]. In this study, we observed that many tumors expressed high levels of both, MDM2 and MDM4.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…MDM2 is another p53 inhibitor present in high levels in HNSC [15][16]. In this study, we observed that many tumors expressed high levels of both, MDM2 and MDM4.…”
Section: Discussionsupporting
confidence: 48%
“…These data suggest that increased levels of MDM2 may substitute for mutations in p53, which represents an alternative mechanism by which tumor cells escape from the tumor suppressive activities of p53. In HNSC, overexpression of MDM2 has been observed [15][16], but a clear correlation between the levels of MDM2 protein and p53 status has not been established [17].…”
Section: Introductionmentioning
confidence: 99%
“…Incubation with the primary antibodies (monoclonal MDM2 antibody, IF-2, Oncogene Science, USA, and monoclonal p53 antibody, DO-7, Novocastra Laboratories, UK), British Journal of Cancer (1997) 75(9), [1302][1303][1304][1305][1306][1307][1308] . Cancer Research Campaign 1997 the enzyme colour reaction, haematoxylin counterstaining and mounting were carried out as described elsewhere (Foulkes et al, 1995;Marchetti et al, 1995a and b;McCann et al, 1995;Ofner et al, 1995;Matsumura et al, 1996). Immunostaining results were assessed, taking into account the cancer cells whose nuclei showed positive immunoreactivity for MDM2 ( Figure 1) or p53 protein.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…In immunohistochemical studies using monoclonal anti-MDM2 protein antibody, the incidence of MDM2 immunohistochemical (over)expression in human cancers has been reported to be 30% in bladder cancers (Lianes et al, 1994), 20% in colorectal cancers (Ofner et al, 1995), 3% in ovarian cancers (Foulkes et al, 1995), 40% in oral carcinoma (Matsumura et al, 1996) and 22-41% in breast cancers (Marchetti et al, 1995b;McCann et al, 1995). In NSCLC, whereas Marchetti et al (1995a) reported that MDM2 oncogene product expression was detected immunohistochemically only in three (6%) patients with gene amplification, it was detected in the present study in 24% of patients, independently of MDM2 gene amplification status.…”
Section: Post-operative Prognosismentioning
confidence: 99%
“…MDM2 is aberrantly expressed in a number of human tumors (12)(13)(14)(15)(16)(17)(18)(19)(20). It forms a negative autoregulatory loop with p53 by binding to its activation domain (21) and inhibiting its functions in transactivation (22)(23)(24), growth arrest (25,26), and apoptosis (26 -28).…”
mentioning
confidence: 99%